Estudo da influência da redução de pressão na interface para extração de iodo com querosene - Císsara Ramalho Silva Brito (2015)
The objective of this study is to evaluate the influence of pressure reduction at interface during separation phase in iodine extraction by kerosene using liquid-liquid extraction, proposing a new piece of equipment to use this technique. Furthermore this study proposes and validates an analytical method for molecular iodine in kerosene by spectrophotometry using a visible region (521 nm). The results indicate a possible influence of the pressure reduction in iodine extraction but the experiments were inconclusive.